Effects of individualized resistance training prescription with heart rate variability on muscle strength, muscle size and functional performance in older women - Bittencourt, Diego; de Oliveira, Ramon Martins; da Silva, Deivid Gomes; Bergamasco, João Guilherme Almeida; Cesar, Marcelo de Castro; Godoi Jacomassi, Daniela; de Camargo, Júlio Benvenutti Bueno; Kingsley, J. Derek; Libardi, Cleiton Augusto (Frontiers in Physiology, 2024)
IntroductionThis study aimed to investigate whether individualizing autonomic recovery periods between resistance training (RT) sessions (IND) using heart rate variability (HRV), measured by the root mean square of successive R-R interval differences (RMSSD), would lead to greater and more consistent improvements in muscle strength, muscle mass, and functional performance in older women compared to a fixed recovery protocol (FIX).MethodsTwenty-one older women (age 66.0 ± 5.0 years old) were randomized into two different protocols (IND: n = 11; FIX: n = 10) and completed 7 weeks of RT. Measurements of RMSSD were performed within a five-day period to establish baseline values. The RMSSD values determined whether participants were recovered from the previous session. The assessments included muscle cross-sectional area (CSA), one-repetition maximum (1RM), peak torque (PT), rate of force development (RFD), chair stand (CS), timed up and go (TUG), 6-minutes walking (6MW), and maximum gait speed (MGS).ResultsThere were no significant (P > 0.05) group vs. time interactions. There were significant main effects of time (P < 0.05) for CSA, 1RM, PT, TUG, CS, 6MW, and MGS, while no significant changes were observed for RFD (P > 0.05).ConclusionIND does not seem to enhance responses in muscle mass, strength, and functional performance compared FIX in healthy older women.